PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APPSHEET PADA MATA PELAJARAN KEPEGAWAIAN DI SMKN 40 JAKARTA - Imelda Bekay Zharya; Christian Wiradendi Wolor; Eka Dewi Utari (STKIP Subang, 2026)
This research is motivated by the suboptimal use of digital learning media in the subject of personnel administration at SMKN 40 Jakarta. The existence of practice-based learning media is expected to influence the understanding and skills of personnel administration of students. This study aims to develop AppSheet-based learning media and analyze the level of validity and practicality. This type of research uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The research subjects involved material experts, media experts, instructional design experts, and class XI students of Office Management SMKN 40 Jakarta. Data collection techniques were carried out through observation, interviews, questionnaires and documentation. Data were analyzed using quantitative and qualitative descriptive techniques. The results showed that the media obtained a validity percentage of material experts of 100%, media experts 93.33%, and instructional design experts 93.75% with an average of 95.69% with a very valid category. The practicality test achieved a 94.11% score in the individual trial and 95.95% in the small group trial, with an average of 95.03%, categorized as very practical. Thus, the AppSheet-based learning media meets the criteria for validity and practicality, making it suitable for use as a learning medium for the civil service subject at SMKN 40 Jakarta.